Feasibility of applying the psychosocial intervention STrAtegies for RelaTives to family caregivers of patients with dementia: a case report. Issue 3 (11th February 2018) - Kashimura, Masami; Nomura, Toshiaki; Ishiwata, Akiko; Kitamura, Shin
Abstract : As the number of people with dementia in Japan continues to rise, family caregivers are experiencing an increasing care burden. Previous research has shown that this care burden can affect family caregivers' physical and mental health. Therefore, providing support for caregivers of family members with dementia has become an urgent issue in the country. The purpose of this study was to investigate the feasibility of applying STrAtegies for RelaTives (START), a psychosocial intervention programme developed in the UK to improve caregivers' moods and quality of life, to Japanese family caregivers. Specifically, in this paper, we provide a detailed description of the application of the Japanese version of START to a female caregiver. Our investigation found that the Japanese version of START is a feasible option for alleviating the mental and physical burden on family caregivers of patients with dementia. This result provides preliminary support for the wider application of START in Japan, as it can decrease care burden and improve the daily lives of caregivers of people with dementia. It also supports the development and implementation of other systems that can provide similar services for other caregivers.